Kualitas Udara Ruangan Akibat Pembakaran Briket Tandan Kosong Sawit - Efpia Naomi Yohana Tambunan; Hafidawati Hafidawati; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Empty palm bunches as the most waste generated from the processing of fresh fruit bunches have the potential to be used as renewable energy source in the form of biomass briquettes. This can be seen form the availability are ±23% from the all process and have thermal energy is ±4.958,46 cal/gr. However, the burning of empty palm bunches briquettes as solid fuel for household can effect the indoor air quality, so need to do study test. In this study will test the gas pollutant CO dan NO2 from the burnng of empty palm bunches briquettes use the adsorbent method with impinger. The test will doing in 1 hour in the room that has 15% surface area ventilation of the floor surface area. The test result will be compared with quality standar PerMenKes RI No. 1077 in 2011. The result show that there 4,75 ppm CO and 0,033 ppm NO2. Based on the result of this study that the burnng of empty palm bunches briquettes with the room that has 15% surface area ventilation of the floor surface area were below quality standar PerMenKes RI No. 1077 in 2011 about Pedoman Penyehatan Udara dalam Ruangan Rumah.Keywords : briquettes, empty palm bunches, indoor air quality, concentrasion of gaseous pollutans.